Riley McGill: capstone - McGill, Riley, artist (Colorado State University. Libraries, 2023)
The artist's statement: I began my journey to design through a passion and background in drawing. My passion for drawing led me to discover hand-lettering which ignited my love for typography. The push to use technology in my art process, and my passion for letters created an easy segue to explore graphic design. When I first began designing, I found great joy and ease being able to apply my traditional art skills/background in a more tangible way, and reaching a wider audience. I do not view design as something purely functional, and I feel there are opportunities for fun, creativity, and true art in most projects.I find that every design is like a puzzle, with each element having its perfect place and purpose in the final work. Because I find my work to be so personal, I enjoy making my work more recognizable by leaning into humor and unique methods/styles that interest me. Keeping my work interesting for myself is important because this greater passion produces more ideas and greater results. In my work, I try to do as much as possible by hand, whether this is illustration, hand-drawn typography, or manipulating physical materials. Along with this I put great intention and emphasis into the typography and colors of my work, aiming for visual interest and cohesion throughout the style and content.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design